Potential contributing factors to upper limb associated reactions in people with acquired brain injury: an exploratory study. Issue 15 (17th July 2022) - Kahn, Michelle B.; Clark, Ross A.; Mentiplay, Benjamin F.; Bower, Kelly J.; Olver, John; Williams, Gavin
Abstract: Purpose: To determine which potential contributing factors are associated with upper limb associated reaction (AR) expression in individuals with acquired brain injury (ABI). Methods: Forty-two participants underwent three-dimensional motion analysis at self-selected walking speed to generate the AR outcome measure, quantifying their upper limb kinematic deviation compared to healthy controls. Clinical assessment included: upper and lower limb hypertonicity, spasticity and strength, balance, dynamic walking stability, arm and leg function, anxiety, arm pain/discomfort, and fear of falling. Results: Significant, moderate-to-strong correlations ( r  = 0.42–0.74, p  < 0.05) existed between upper limb ARs and both hypertonicity and spasticity of the upper limb muscles and the knee extensors. Significant, moderate correlations to ARs ( r  = 0.42–0.59, p  < 0.05) existed for balance, dynamic stability, upper limb strength, and arm function. The severity of AR was significantly different between those with and without hypertonicity of the four tested upper limb muscles, elbow and long finger flexor spasticity, knee extensor spasticity, and reduced dynamic stability ( p  < 0.05; effect sizes ≥0.80). However, these contributing factors were not present in all participants. Conclusions: Associated reactions are complex and multi-factorial. There were several significant correlations indicating that factors may influence AR severity. While positive upper motor neuron syndrome features should be prioritised for clinical assessment, these factors are not prerequisites for ARs. IMPLICATIONS FOR REHABILITATION: Upper limb associated reactions are a complex and multi-factorial phenomenon. Upper limb muscle hypertonicity and spasticity should be prioritised for assessment; however, they are not prerequisites for associated reactions. Hypertonicity and spasticity should be differentiated as they may have differing relationships to associated reactions. Knee extensor hypertonicity and spasticity, postural stability, upper limb strength, and arm function may also be contributing factors to consider.